The Cropping Pattern Design for Irrigated Area (Case Study in Molek Irrigation That Using Solver Program) - Rahadi, Bambang; Hastari, Sri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The Molek irrigated area is watered from Blobo dam with discharge range 6811.106 1/s to 7563.470 1/s that watering farming area of 3974 ha, with the labor of 33219 HP/periode and the tractor power of 48619 HP/period. The water availability, labor, and land area are limited resources, therefore it is the reason why the optimum management is needed to gain maximum profit. Solver program that is set in extention microsoft exel can be used for optimation. The aim of this research is to find out optimalization cropping pattern and maximum profit of the the limited water availability, labor, and land area.The study showed that Molek irrigated had optimum cropping pattern as followed: (1) Paddy¬-paddy-paddy cropping pattern was 3400 ha, paddy-paddy-palawija was 305 ha, suger cane was 49 ha, (2) The maximun profit of the three patterns was Rp. 115.196.679.500, (3) The water availability and labor in Molek irrigated was sufficient for the pattern of paddy-paddy-paddy of 3400 ha.Keywords: optimation, cropping pattern, water availability